Ekplanasi Ilmiah Metode Hipnotis terhadap Otak Manusia - Muhyiatul Fadilah (Undiksha, 2018)
Hypnotic is a method to explore humans’ conscious mind in order to experience suggestion alteration following particular purpose. Previously, in Indonesia, hypnotic was dominantly known as one on crimes technique to rob the victims easily in short time. Then, public perception shifted after hypnotic action performed in stages to entertaintaudience. Recently, hypnotic has been applied to benefit patient, students or individual with biological and psychological pains. Unfortunately, the existence of hypnotic as a logical explanation have not been available in a comprehensible text for public understanding, although excessive empirical studies existed in multidiscipline ways. This review article propose a scientific explanation toward hypnotic and its application such medical and educational purposes, based on a scientific philosophy. To conclude, hypnotic concept developed according to Deductive-Nomologies Explanation Scientific Model and fulfill positivistic and naturalistic truth paradigm and pragmatic truth theory. Its brief scientific explanation that is hypnotic processes with support of brain structure and mechanism. Scientific terms and concepts which are been involved are cerebrum, autonomous nervous system, reticular activating system, medulla oblongata, brainstem, corpus collosum, brain wave frequencies alteration, and chemically control of serotonine and endorphin.